2019
DOI: 10.1039/c8nr08511k
|View full text |Cite
|
Sign up to set email alerts
|

Powder exfoliated MoS2 nanosheets with highly monolayer-rich structures as high-performance lithium-/sodium-ion-battery electrodes

Abstract: The proposed powder exfoliated monolayer-rich MoS2 electrode exhibits remarkable specific capacities and stable cyclic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 78 publications
3
56
0
Order By: Relevance
“…Interestingly, the magnified profile of the (002) signal for SeVs‐MoSe 2 shows a slight peak shift toward a lower angle in comparison with the pristine one, possibly owing to the partial re‐stacking of nanosheet powders when conducting the measurement (Figure S8). Similar phenomenon can be found in MoS 2 [14] . Meanwhile, Raman spectrum of SeVs‐MoSe 2 readily manifests a red shift of A 1g mode at 243 cm −1 (Figure S9).…”
Section: Resultssupporting
confidence: 77%
“…Interestingly, the magnified profile of the (002) signal for SeVs‐MoSe 2 shows a slight peak shift toward a lower angle in comparison with the pristine one, possibly owing to the partial re‐stacking of nanosheet powders when conducting the measurement (Figure S8). Similar phenomenon can be found in MoS 2 [14] . Meanwhile, Raman spectrum of SeVs‐MoSe 2 readily manifests a red shift of A 1g mode at 243 cm −1 (Figure S9).…”
Section: Resultssupporting
confidence: 77%
“…Similar phenomenon can be found in MoS 2 . [14] Meanwhile,R aman spectrum of SeVs-MoSe 2 readily manifests ar ed shift of A 1g mode at 243 cm À1 (Figure S9). The appearance of Se vacancies results in partial change in the bond length of Se-Mo-Se as well as the corresponding crystal lattice parameters.With respect to the SVs-MoS 2 (Figure 2f), the Raman spectrum displays red-shifted signals at 386 and 412 cm À1 ,r espectively matching the out-of-plane A 1g and inplane E 1 2g mode.…”
Section: Resultsmentioning
confidence: 96%
“…He further suggested that by controlling the spatial geometry, rate performance and stability for Na + intercalation can be enhanced. In their work, Li et al [ 64 ] suggested that by tailoring the size of MoS 2 , which is increased up to the nanoscale fraction of edges, these powder‐exfoliated MoS 2 nanosheets (EF‐MoS 2 ) (fabricated via a facile sonication process, as shown in Figure 4h) can effectively be exfoliated into the monolayer structure. They also suggested that these nanosheet structures (Figure 4i), acting as an anode material for Na + storage, showed a high reversible capacity of 385 mAh g −1 at a current density of 2 A g −1 after 100 cycles and a high‐rate reversible cyclic stability of 248 mAh g −1 at a very high current density of 5 A g −1 after the same number of cycles, as shown in Figure 4j.…”
Section: Mos2‐based Nanostructures As An Anode Materials For Sibsmentioning
confidence: 99%